Effect of time of sowing and spacing on seed yield and quality of hybrid seed production in castor (Ricinus communis L.): Effect of time of sowing and spacing on seed yield and quality of hybrid seed production in castor (Ricinus communis L.) - P ARUTCHENTHIL,; S R VENKATACHALAM,; P KATHIRVELAN,; M DEIVAMANI, (Journal of Oilseeds Research, 2020)
The parental lines, DPC-9 (female) and TMV-5 (male) of castor hybrid (YRCH-1) were sown in 3:1 ratio withsix sowing dates and four different spacings. The highest seed yield was recorded from first fortnight of November or second fortnight of November adopting either 120 cm x120 cm or 150 cm x 120 cm. The genetic contamination in terms of interspersed male flowers present in the female lines was minimum during the Novembersowing.